Standard Tests Usefulness in Diagnosing Myocardial Ischemia, Alone or With Combination in Type 2 Diabetic Patients (Iraqi Journal of Medical Sciences, 2024)
Background: Despite the recognition of myocardial ischemia as a unique clinical condition, there is still substantial debate on the suitable screening protocols for individuals who are at high risk for cardiac insult.Objective: To examine effectiveness of already used medical diagnostic tests in identifying myocardial ischemia in type 2 diabetic individuals.Methods: Case control research included 50 type 2 diabetic patients and a control group of 50 healthy volunteers. All participants were investigated using: exercise treadmill test (TMT), 24-hour Holter monitoring, echocardiography, electrocardiography (ECG), lipid profile, HbA1c, renal function test, and complete blood picture.Results: Myocardial ischemia was more common in males (54%), with no statistical difference in body mass index (BMI). Regarding presence of atherogenic risk factors, there was a statistically significant difference in hypertension, smoking but no statistically significant difference in hyperlipidemia. Using test combination was better than using one test alone in early diagnosis of myocardial ischemia. Concordance between TMT and Holter monitoring was the highest one in comparison to other combinations of tests.Conclusion: Diabetes mellitus itself was the major cause of ischemic heart disease rather than the other atherogenic risk factors. The combination of the three non-invasive tests in detection of myocardial ischemia give the best results, but if only two of them to be done, then it is better to select the combination with best agreement. TMT has the greatest role when combined with another test in detection of myocardial ischemia, while echocardiography has the weakest role in this regard.Keywords: Myocardial ischemia, diabetes mellitus, treadmill test, echocardiography, Holter monitoringCitation: Yousif ZY, Al-Hashimi AF, Hamid MB. Standard tests usefulness in diagnosing myocardial ischemia, alone or with combination in type 2 diabetic patients. Iraqi JMS. 2024; 22(2): 229-238. doi: 10.22578/IJMS.22.2.7
Keywords: Myocardial ischemia; diabetes mellitus; treadmill test; echocardiography; Holter monitoring